Ultrastructure and histochemistry of the digestive gland of the giant predator snail Adelomelon beckii (Caenogastropoda: Volutidae) from the SW Atlantic. Issue 2 (April 2015) - Arrighetti, F.; Teso, V.; Penchaszadeh, P.E.
Highlights: Two types of cells were found in the digestive gland of Adelomelon beckii. Digestive cells are involved in intracellular digestion via endocytotic processes. Vacuolated cells seem to be responsible for protein secretion. Both cells are subject to cyclical changes related to their feeding activity. Feeding type does not influence the morphology of the digestive gland. Abstract: This study deals with the structure of the digestive gland of the carnivorous gastropod Adelomelon beckii in Mar del Plata area (Argentina) and discusses the function of its cell types and compare with other gastropods. According to histological and transmission electron microscopy observations the epithelium is composed of two types of cells that are subject to cyclical changes, involving three phases: absorption, digestion and fragmentation. The majority of the cells, called digestive cells, have a basal nucleus with a cytoplasm filled by spherical digestive vesicles in different stages. The apical pole of the cell is covered with microvilli and cilia and shows evidence of endocytotic activity during the absorption phase. The intracellular digestive process passes through: (1) fusion of endocytotic vesicles; (2) transformation in heterolysososmes by fusion with enzyme-rich vesicles; (3) formation of residual bodies after digestion, which are pinched off to the lumen gland during fragmentation phase. The second type of cell in the acini are called vacuolated cells, which occur in clusters, the nucleus is in the mid-basal region and the cytoplasm is basophilic, filled with stacks of RER. During the absorption phase the vacuolated cells secrete neutral mucins that probably serve as lubrication to facilitate transport of food particles. During all phases, a large amount of lipofuscin, an insoluble pigment that is accumulated after lysosome digestion, is accumulated. The functional morphology of the different cell types found in this carnivorous gastropod is very similar to that found in herbivorous and deposit-feeding gastropods, which suggests that the feeding type does not influence the micro-morphology of the digestive gland.